Analysis of Ciheras Beach Wind Potential for Minimal Pollutant Electrical Energy Generation - Adi Nugraha; Agus Ramelan; Nike Sartika (Universitas Sebelas Maret (UNS), 2023)
Pollutant is a serious problem today as the use of non-renewable energy sources is still a favorite, especially those sourced from coal and petroleum fuels. To anticipate dependence on coal-fired power plants, many studies have been conducted related to environmentally friendly power plants. One of the environmentally friendly power plants is wind power plants. Based on the criteria of wind turbines such as TSD-500, a wind speed of at least 3 m/s is required to start production. The purpose of this study is to find out how much potential clean energy is generated through wind energy generation on the coast of Ciheras. The research method in data collection used is qualitative descriptive. The results of the analysis found that the energy obtained from the process of converting wind energy into electrical energy can illuminate 9 houses, with each house consuming 70 Watts of power for 5 hours.